AMERICAN MANUFACTURING, AMERICAN TECHNOLOGY AND THE LABOR QUESTION AT THE PARIS EXPOSITION UNIVERSELLE OF 1867 - Gregory Zieren (Essays in Economic and Business History, 2004)
The Paris Exposition Universelle of 1867 was devoted to the theme, “The History of Labor,” and awarded special prizes to firms with paternalistic labor policies to promote harmony between workers and employers. The guiding spirit of the Exposition and its labor theme was the French social thinker, Frédéric Le Play. American technology was a second trend on view at the Exposition, and American firms, including the Pacific Mills of Lawrence,MA won gold medals and international recognition.